CPX-351: a nanoscale liposomal co-formulation of daunorubicin and cytarabine with unique biodistribution and tumor cell uptake properties - Mayer LD (Dove Medical Press, 2019)
Lawrence D Mayer, Paul Tardi, Arthur C LouieJazz Pharmaceuticals, Inc., Palo Alto, CA, USAAbstract: Combination regimens are a standard of care for many cancers. However, components of such regimens are typically first developed individually and subsequently combined using strategies to minimize toxicity. Little or no consideration is given to strategies that potentially maximize efficacy. In contrast, CPX-351 (Vyxeos®) is a dual-drug liposomal encapsulation of cytarabine and daunorubicin that was rationally designed to improve efficacy over the traditional 7+3 cytarabine/daunorubicin chemotherapy regimen for patients with acute myeloid leukemia (AML). The notable clinical efficacy of CPX-351 is achieved through maintenance of a synergistic 5:1 molar ratio of cytarabine and daunorubicin within the liposome after intravenous injection. The CPX-351 liposome, which is formulated to contain bilayers of distearoylphosphatidylcholine, distearoylphosphatidylglycerol, and cholesterol at a 7:2:1 molar ratio and remains in a gel phase at body temperature, provides stability without polyethylene glycol, controlled release of cytarabine and daunorubicin, limited systemic drug distribution, and preferential internalization within malignant myeloblasts in the bone marrow via active uptake of liposomes into cytoplasmic vacuoles. Thus, the CPX-351 liposome protects cytarabine and daunorubicin from metabolism and elimination, while overcoming pharmacokinetic differences between the two agents. In clinical studies, these liposome properties markedly increased the elimination half-life of CPX-351 versus free cytarabine and daunorubicin and maintained a synergistic drug ratio for over 24 hrs after administration. Preferential uptake of liposomes by leukemia cells suggests that relatively large amounts of cytarabine and daunorubicin enter malignant cells via liposomes, potentially bypassing P-glycoprotein-based efflux pumps, which are important mediators of chemotherapy resistance, and contribute to the rapid clearance of leukemia cells from the circulation and bone marrow. These pharmacologic advantages, a direct consequence of properties of the encapsulating liposome, may explain the efficacy of CPX-351 in patients with newly diagnosed high-risk/secondary AML and the reduced drug exposure in off-target tissues that contribute to a manageable safety profile.Keywords: acute myeloid leukemia, CPX-351, cytarabine, daunorubicin, molar ratio, nanoscale liposomes